(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
In the article influence is examined on forming of world view of poet of tragic vital and creative way, originality and uniqueness of poetics of color, unicity of attitude and attitude of poet, theme of traklivskoy lyric poetry, innovation of Georga Traklya in the area of poetic language.